Crop model usefulness in drylands of southern Africa: an application of DSSAT - (:unkn) unknown (My University, 2015)
Crop models are useful tools for simulating impacts of climate and agricultural practices on crops. Models have to demonstrate the ability to simulate actual crop growth response in particular environments before application. Data limitations in southern Africa frequently hinder adequate assessment of crop models before application. The DSSAT model was used to test the usefulness of crop models under data limited dryland conditions of southern Africa by validation using data from experimental trial reports and district-wide crop yield estimates. Two crops each were selected in three locations to represent varying cropping and physical conditions in southern Africa i.e. maize and sorghum (Mohale’s Hoek - Lesotho and Big Bend - Swaziland) and maize and groundnut (Lilongwe - Malawi). Results showed that DSSAT performs well in simulating crop yields obtained from experimental trials. District wide simulated mean crop yields were acceptable (relative difference ranged from -12.2 % to +2.36 %). However, the model’s capture of seasonal yield variation for some locations and crops was uncertain, due to climate extremes. It was concluded that satisfactory crop model testing before application is possible and that DSSAT crop models are useful even under data limited conditions.
Keywords: African Research